1994
DOI: 10.1007/bf00203218
|View full text |Cite
|
Sign up to set email alerts
|

Titanium substitution and OH-bearing defects in hydrothermally grown pyrope crystals

Abstract: Abstract.A series of Ti-substituted pyrope crystals was synthesized in the system MgO-(Na20) -A1203 -TiO2 -SIO2-H20 at Pa20=Ptot between 25 and 30 kbars and 975 and 1000 ~ C, using graphite heated piston-cylinder devices. The crystals, ranging up to 500 gm in diameter, were studied by X-ray, electron-microprobe and FTIRmicroscope spectrometric techniques. The pyrope crystals were colourless when hem/rot or mt/wu buffers were used during the synthesis, and pale blue with the wu/iron buffer and in unbuffered run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Incorporation of hydroxyl in the garnets described here would be consistent with the concept of precipitation of crack-healing garnet aided by an aqueous fl uid. Beran (1996) concluded that incorporation of defect hydroxyl in nominally anhydrous, close-packed silicate structures requires associated vacancies in the cation sites, for example vacancies at octahedral Cr or Al sites (Andrut et al 2002), or on tetrahedral sites associated with substitution of octahedral Ti for tetrahedral Si and octahedral Al (Khomenko et al 1994). Spatial variability of hydroxyl concentration within individual garnet grains has been resolved using FTIR spectroscopy by Khomenko et al (1994).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Incorporation of hydroxyl in the garnets described here would be consistent with the concept of precipitation of crack-healing garnet aided by an aqueous fl uid. Beran (1996) concluded that incorporation of defect hydroxyl in nominally anhydrous, close-packed silicate structures requires associated vacancies in the cation sites, for example vacancies at octahedral Cr or Al sites (Andrut et al 2002), or on tetrahedral sites associated with substitution of octahedral Ti for tetrahedral Si and octahedral Al (Khomenko et al 1994). Spatial variability of hydroxyl concentration within individual garnet grains has been resolved using FTIR spectroscopy by Khomenko et al (1994).…”
Section: Discussionmentioning
confidence: 97%
“…Beran (1996) concluded that incorporation of defect hydroxyl in nominally anhydrous, close-packed silicate structures requires associated vacancies in the cation sites, for example vacancies at octahedral Cr or Al sites (Andrut et al 2002), or on tetrahedral sites associated with substitution of octahedral Ti for tetrahedral Si and octahedral Al (Khomenko et al 1994). Spatial variability of hydroxyl concentration within individual garnet grains has been resolved using FTIR spectroscopy by Khomenko et al (1994). A similar type of coupled substitution in zircon in which Y and REE replace Zr, balanced by hydroxyl and vacancy defects, has been proposed as the source of cathodoluminescent emission (Ohnenstetter et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Ti in aluminous garnet is generally higher at higher pressures (P) and/or higher temperatures (T), although there is considerable variation and Ti P-T relationships are complicated (e.g., Khomenko et al 1994;Ono 1998;Massonne and Brandelik 1998;; Kawasaki and Motoyoshi 2007;Hermann and Spandler 2008;Konzett and Frost 2009;Auzanneau et al 2010;Proyer et al 2013). Ti generally is thought to go into the octahedral site of garnet, but can also enter the tetrahedral site (e.g., Malitesta et al 1995;Massonne and Brandelik 1998;Ackerson et al 2013;Proyer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Principally, they should occur here as an overlap between the respective bands originating from Ti 3 § in the pyrope and rutile matrix as well. The increasing absorbance below 16000 cm -1 is typical of defect-bearing rutiles (Johnson et al 1968;Becker 1993, personal communication;Khomenko et al 1994). The most remarkable feature of the spectra of pyropes with rutile inclusions is the stepwise increase of absorbance in the UV, indicating the presence of two absorption edges (Fig.…”
Section: Optical Absorption Spectra and Their Interpretationmentioning
confidence: 95%